MORPHOLOGY AND WEIGHT OF AFRICANIZED QUEEN BEES PRODUCED IN DIFFERENT DIAMETERS OF ARTIFICIAL, CUPS - Morini, MSD; Bueno, O. C. (Assn Advan Zoology, 1993)
The present work showed that the newly emerged queen weight, the number of ovarioles. and the spermatheca mass are not influenced by the sizes of the wax cups. The first two characters suffered time transference influence, and the best acceptances were obtained mainly, in wax cups with diameters of 7, 8, and 9 min.